2009
DOI: 10.1158/1078-0432.ccr-08-3270
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of αvβ3 Expression by a Bifunctional Chimeric RGD Peptide not Cross-Reacting with αvβ5

Abstract: Purpose: To test whether a novel bifunctional chimeric peptide comprising a cyclic ArgGly-Asp pentapeptide covalently bound to an echistatin domain can discriminate α v β 3 from α v β 5 integrin, thus allowing the in vivo selective visualization of α v β 3 expression by single-photon and positron emission tomography (PET) imaging. Experimental Design: The chimeric peptide was preliminarily tested for inhibition of α v β 3 -dependent cell adhesion and competition of 125

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
63
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 42 publications
(71 citation statements)
references
References 38 publications
8
63
0
Order By: Relevance
“…64 Imaging ligands for α v β 3 are available, and have been used in PET studies in animal models of cancer. 65 The inverse correlation between α v β 3 expression and endothelial permeability suggests that this molecule is downregulated in conditions of microvascular leak, and that examining its expression in patients with sepsis would be of great interest.…”
Section: Endothelial Activationmentioning
confidence: 99%
“…64 Imaging ligands for α v β 3 are available, and have been used in PET studies in animal models of cancer. 65 The inverse correlation between α v β 3 expression and endothelial permeability suggests that this molecule is downregulated in conditions of microvascular leak, and that examining its expression in patients with sepsis would be of great interest.…”
Section: Endothelial Activationmentioning
confidence: 99%
“…16 RGD peptide conjugated with nanomaterials enabled tracing of glioma in a photoinduced electron transfer imaging system. [17][18][19] We found that RGD and c(RGDfC) polyionic complex micelles, but not vehicle control or polyionic complexes, induced apoptosis of human glioma cells in vitro.…”
Section: Discussionmentioning
confidence: 87%
“…Levels of αvβ3, αvβ5, αIIbβ3 and α5β1 integrins were determined by fluorescence-activated cell sorting (BD FACSAria II, Franklin Lakes, NJ, USA) [29]. Briefly, selected cell lines (5 × 10 5 ) were incubated with FITC-conjugated mouse antibodies LM609 (Merck KGaA, Darmstadt, Germany), P1F6 (Merck KGaA) and A2A9/6 (Santa Cruz, Dallas, TX, USA) recognizing ανβ3, ανβ5 and αIIbβ3 integrins, respectively, for 1 h at 4 °C in the dark.…”
Section: Methodsmentioning
confidence: 99%